WE PREPARE OUR STUDENTS FOR TEACHING THE FUTURE GENERATION - Agus Widyantoro (Universitas Ahmad Dahlan)
Lecturers in universities preparing for future teachers often teach materials which they think are up-to-date. However, is it true that what they teach may be useful for their students in their teaching in the future. Students may graduate in four to five years and they may not get jobs as soon as they leave universities. When they get a job as teachers, it might be five to six years after they graduate. At that time in schools, a new curriculum may be introduced, new theories on language teaching may emerge, and new problems may be faced. What they got from their lecturers in universities may not be relevant for solving the new problems. So, they need new knowledge or even new skills. This paper tries to explore the ways lecturers can do to prepare their students to face the ‘real’ challenges in their time of teaching.